Clinician and patient perspectives on the ontology of mental disorder: a qualitative study - Kohne, Annemarie Catharina Johanna; de Graauw, Lukas Peter; Leenhouts-van der Maas, Reina; Van Os, Jim (Frontiers in Psychiatry, 2023)
Background: Psychiatry may face an “identity crisis” regarding its very foundations. The lack of consensus regarding the theoretical grounds of psychiatry as a discipline has its epicenter in the discussion about the Diagnostic and Statistical Manual (DSM). A growing number of academics considers the manual broken and a growing number of patients voice concern. Despite the huge body of critique, 90% of Randomized Trials are based on DSM definitions of mental disorder. Aims: We aim to identify ontologies that live amongst patients and clinicians, evaluate the degree of consistency and coherence between clinician and patient views and contribute to the establishment of a novel ontological paradigm of mental disorder that is aligned with patients’ and clinicians’ perspectives. Method: 80 participants (clinicians/patients/clinicians with lived experience) were interviewed using a semi-structured interview, exploring their ideas on the ontology of mental disorder. Interviews were transcribed and analyzed using inductive Thematic Analysis. Results: From all subthemes and main themes, a typology was constructed in which six, not necessarily mutually exclusive, ontological domains were identified: mental disorder as (1) disease, (2) functional impairment, (3) loss of adaptation, (4) existential problem, (5) highly subjective phenomenon, and (6) deviation from social norms. Common ground for the sample groups was that mental disorder is about functional impairment. Although about a fourth of sample clinicians holds an ontological concept of disease, only a small percentage of patients and none of the clinicians with lived experience adhered to an ontological concept of disease. The sample clinicians most often understand mental disorder to be a highly subjective phenomenon, and individuals with lived experience (patients and clinicians) most often understand mental (dis)order to be adaptational in nature: an (im)balance of burden in relation to strengths, skills, and recourses. Conclusions: The ontological palette is more diverse than what is taught about mental disorder in dominant scientific and educational discourse. Investment is required in the development, elaboration and coming of age of these alternative ontologies, allowing them to reach their full potential and act as drivers of a landscape of promising novel scientific and clinical approaches.